Aqueous extraction of red seaweed bioactive compounds and synthesis of silver nanoparticles for agriculture applications - Thynraj Antony Roseline; Muthiyal Prabakaran Sudhakar; Kulanthaiyesu Arunkumar (Journal of Agriculture and Food Research, 2023)
In this study, an aqueous extract of Gracilaria crassa and Grateloupia lithophila was used for the green synthesis of silver nanoparticles (AgNPs) to control plant disease and support plant growth. The synthesised AgNPs were characterised using a UV–visible spectrophotometer, FTIR, XRD, SEM, EDAX, TEM and DLS analysis. The TEM image revealed that synthesised nanoparticles with average size of 51 nm and 20 nm were observed in G. crassa and Grateloupia lithophila extract, respectively. The green synthesised AgNPs exhibited a strong antibacterial activity against Xanthomonas axonopodis pv. citri and Xanthomonas oryzae pv. oryzae, and investigated the effect of biogenic AgNPs on seed germination and seedling growth of rice plants (Oryzae sativa L). Both the sizes (51 and 20 nm) of AgNPs treatments (50 μg/ml conc.) resulted in the highest seed germination rate (98 and 99%), longer roots (17.51 ± 0.50 and 17.68 ± 0.10 cm) and shoot lengths (5.68 ± 0.12 and 6.18 ± 0.10 cm), and produced higher amount of fresh (8.98 ± 0.34 and 9.00 ± 0.14 mg) and dry (3.68 ± 0.05 and 3.80 ± 0.12 mg) biomass weights. On the other hand, rice seedlings treated with both sizes of AgNPs, particularly at 100 μg/ml concentration, responded with a lower rate of seed germination, shorter root and shoot length and a lower amount of fresh and dry biomass weight was observed. The nanocomposites synthesised from Grateloupia lithophila (20 nm) were more effective in seed germination and seedling growth than G. crassa (51 nm) nanocomposites. In this study, one-step synthesised AgNPs from red seaweeds extracts controlled the bacterial pathogens causing disease in rice and promoted the growth of the plant.